Estabilidade do guacamole refrigerado elaborado com abacate ‘hass’ e diferentes formulações - Daiuto, Erica Regina [UNESP]; Vieites, Rogério Lopes [UNESP]; Vileigas, Danielle Fernandes [UNESP]; Lidia, Raquel Carvalho [UNESP] (My University, 2012)
Avocado is a nutritious fruit with qualities that make possible the increase in his consumption. Processed avocado is an alternative, but, a challenge, not only for the technological diffi culties in to maintain the product quality as well as to please the consumer’s palate still no habituated it this consumption form. The objective of this research was to evaluate the guacamole stability elaborated with different formulations being conserved under refrigeration, to obtain a product with characteristics and quality of fresh. Guacamole was elaborated with ‘Hass’ avocado, being accomplished three treatments that differed for the lemon, ascorbic acid and citric acid addition. Product was conditioned in nylon+ polyethylene packages, with and without vacuum application and stored under refrigeration (4o C±1). Evaluation of sensorial parameters, color, pH and acidity was accomplished to the 0, 3, 7 and 10 days of storage. Formulation that contained just lemon was the most unstable as for the appraised parameters during the refrigerated storage and the samples stayed acceptable to consumption just until the seventh day. Avocado product can preserve his natural and fresh aspect elaborated with citric and ascorbic acid, being stored under refrigeration in nylon+ polyethylene packages.

O abacate é um fruto nutritivo com qualidades que viabilizam o aumento de seu consumo. O abacate processado é uma alternativa, mas, um desafi o, não somente pelas difi culdades tecnológicas em se manter a qualidade do produto como também agradar o paladar do consumidor ainda não habituado a esta forma de consumo. O objetivo desta pesquisa foi avaliar a estabilidade do guacamole elaborado com diferentes formulações sendo conservado sob refrigeração, para obter um produto com características e qualidade de fresco. O guacamole foi elaborado com abacate ‘Hass’, sendo realizados três tratamentos que diferiram pela adição de limão, ácido ascórbico e ácido cítrico. O produto foi acondicionado em embalagens de nylon+polietileno com e sem aplicação de vácuo e armazenado sob refrigeração (4oC±1). Avaliação dos parâmetros sensoriais, cor, pH e acidez foi realizada aos 0, 3, 7 e 10 dias de armazenamento. A formulação que continha apenas limão foi a mais instável quanto aos parâmetros avaliados durante o armazenamento refrigerado e as amostras permaneceram aceitáveis ao consumo até o sétimo dia. O produto de abacate pode preservar seu aspecto natural e fresco elaborado com ácido cítrico e ascórbico, sendo armazenado sob refrigeração em embalagens de nylon+polietileno.
Stability of refrigerated guacamole elaborated with ‘Hass’ avocado and different formulations
Keywords: Persea americana Mill; Processamento; Qualidade; Minimamente processado